Ploidy manipulations and genetic markers as tools for analysis of quantitative trait variation in progeny derived from triploid plantains - Ortíz, R.; Craenen, K.; Vuylsteke, D.R. (Springer, 1997)
Plantains (Musa spp. AAB group) are starchy bananas widely grown in Africa and tropical America by small landholders. Genetic analysis of the plantain genome is difficult due to its triploidy and high sterility. Ploidy manipulations (scaling up and down the number of chromosomes) and interspecific plantain‐banana hybridization opened the path for the genetic amelioration of the crop and for the investigation of its genome for further manipulations. This report shows the associated effects of ploidy and of the major loci controlling vegetative fruit parthenocarpy and resistance to black sigatoka fungal leaf spot on growth and yield characteristics of plantain‐banana euploid hybrids. The number of copies of the black sigatoka resistance allele (bs1) and of the fruit parthenocarpy gene (P1) in addition to their intralocus interaction and ploidy level were all found to significantly affect bunch and fruit characteristics in euploid plantain‐banana hybrids. Epistasis significantly affected fruit weight and size in one cross but not in another. Significant multiple regression models combining ploidy and genetic markers explained 15 % to 85 % of quantitative trait variation (QTV). The amount of QTV accounted by ploidy and genetic markers varied according to the characteristic and cross in which the markers were examined.